2009
DOI: 10.1158/1078-0432.ccr-09-0632
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutation Associates with Improved Outcome in Breast Cancer

Abstract: Purpose: In breast cancer, somatic mutations in the PIK3CA gene are common. The prognostic implication of these activating mutations remains uncertain as moderately sized studies have yielded variable outcomes. Our aim was to determine the prognostic implications of PIK3CA mutations in breast cancer. Experimental Design: Archival formalin-fixed paraffin-embedded primary breast tumors, from 590 patients selected for known vital status with a median follow-up of 12.8 years and a tumor >1 cm, were genotyped for P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

41
288
8
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 357 publications
(340 citation statements)
references
References 43 publications
41
288
8
3
Order By: Relevance
“…The role of PIK3CA mutations as markers of tumor progression in DCIS is uncertain. PIK3CA mutations in invasive breast cancers have been associated with favorable tumor features 41 and better prognosis in patients with ERpositive, HER2-negative tumors; 40 however, we saw no association of PIK3CA mutations with clinicopathological features in our cohort.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The role of PIK3CA mutations as markers of tumor progression in DCIS is uncertain. PIK3CA mutations in invasive breast cancers have been associated with favorable tumor features 41 and better prognosis in patients with ERpositive, HER2-negative tumors; 40 however, we saw no association of PIK3CA mutations with clinicopathological features in our cohort.…”
Section: Discussioncontrasting
confidence: 65%
“…4,5,40,41 The relatively small number of cases included in this and other DCIS each studies (involving between six and 202 cases), 7,8,14,15,38,39 may account for the variation in prevalence. Alternatively, the high read-depth of our targeted sequencing may have led to increased detection rates compared with exome or Sanger studies: four DCIS cases had a PIK3CA variant frequency of o20%, which could have been missed by less sensitive methods.…”
Section: Discussionmentioning
confidence: 93%
“…[8][9][10][11] In recent large studies of estrogen receptor-positive tumors, the presence of activating PIK3CA hotspot point mutations has been paradoxically associated with more favorable outcome as compared with breast carcinomas with wild-type PIK3CA. 3,12,13 We and other groups have previously shown that the PIK3CA genotype is concordant between ductal carcinoma in situ (DCIS) and concurrent invasive carcinoma in 66-100% of tested samples. [14][15][16][17] However, several small studies suggest that pre-neoplastic or benign breast lesions, such as papillomas, radial scars, or columnar cell lesions, may also very frequently harbor PIK3CA mutations.…”
mentioning
confidence: 93%
“…Activating mutations in the phosphatidylinositol-3-kinase catalytic subunit (PIK3CA) are present in B25% of invasive carcinomas and are present in an even higher percentage (on the order of 40%) of low-grade estrogen receptorpositive carcinomas (luminal A intrinsic subtype). [1][2][3][4][5][6][7][8][9][10] PIK3CA mutations cluster in 'hotspots' in exon 9 (helical domain, E542K and E545K) and exon 20 (kinase domain, H1047R/L). [1][2][3][4][5][6][7][8][9][10] In addition, this pathway is activated by mutations in the plekstrinhomology domain of AKT1 in B5% of breast carcinomas, by the loss of the phosphatase PTEN (phosphatase and tensin homolog on chromosome 10), or rarely by amplification or alterations in other regulatory subunits, and is a target of active drug development.…”
mentioning
confidence: 99%
See 1 more Smart Citation